EXPLORING MOTION CAPTURE ALGORITHMS IN COMPUTER VISION USING INTEL DEPTH CAMERA (Multidisciplinary Journal of Science and Technology, 2024)
The analysis of existing approaches to tracking the human body revealed the presence ofproblems when capturing movements in a three-dimensional coordinate system. The promise ofmotion capture systems based on computer vision is noted. Existing research on markerless motioncapture systems only considers positioning in 2D space. Therefore, the goal of the study was toimprove the accuracy of determining the coordinates of the human body in three-dimensionalcoordinates by developing a motion capture method based on computer vision and triangulationalgorithms